2009
DOI: 10.1183/09031936.00082207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Allergies in Turkey (PARFAIT): results of a multicentre cross-sectional study in adults

Abstract: The Prevalence and Risk Factors of Allergies in Turkey (PARFAIT) study was planned to evaluate the prevalence of and risk factors for asthma and allergic diseases in Turkey.The present analysis used data from 25,843 parents of primary school children, obtained from a cross-sectional questionnaire-based study.A total of 25,843 questionnaires from 14 centres were evaluated. In rural areas, the prevalences asthma, wheezing, allergic rhinitis and eczema in males were: 8.5% (95% confidence interval (CI) 7.9-9.1%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 23 publications
5
53
0
10
Order By: Relevance
“…On the other hand, the risk factors for allergic rhinitis were found to be a family history of allergy, living in a shanty and humid house, and smoking [5], and for atopic dermatitis, they were a family history of allergy; smoking; living in a shanty, garden, or detached house; having good economic conditions; and a high level of education [8,12]. In our study, that many well-known factors, like a family history of allergic diseases, were found to be insignificant in the risk analysis might have resulted from unreliable responses given to the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the risk factors for allergic rhinitis were found to be a family history of allergy, living in a shanty and humid house, and smoking [5], and for atopic dermatitis, they were a family history of allergy; smoking; living in a shanty, garden, or detached house; having good economic conditions; and a high level of education [8,12]. In our study, that many well-known factors, like a family history of allergic diseases, were found to be insignificant in the risk analysis might have resulted from unreliable responses given to the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of these diseases is usually lower in underdeveloped regions but higher in industrialized countries [3]. Environmental factors, such as increased industrialization, air pollution, childhood infections, tobacco smoke, feeding habits, and allergens, affect the prevalence of asthma [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…[84] Betonarme, izocamlı, santral ısıtmalı ve görü-nür şekilde küf bulunan evlerde yaşayanlarda risk artmaktadır. [11,36,85,86] Ev içinde fosil yakıt ve biyogaz kullanımı riski artırırken odun/kömürle ısınmanın genelde riski artırmadığı bildirilmiş-tir. [86,87] Aile ve anne-babanın sosyoekonomik düzeyi arttıkça risk artmakta, evde kardeş sayısı arttık-ça risk azalmaktadır.…”
Section: Ev Ortamıunclassified
“…[6][7][8][10][11][12][13]47,85] Sonuç olarak, son literatür verileri ışığında; AR prevalansının ülke ve bölgelere göre farklı bulunmasının, değişen genetik, diyet, yaşam tarzı ve çevresel nedenlere ilaveten bazı enfeksiyon ve spesifik hastalıkları geçirmeye bağlı olduğu görülmektedir. Dolayısıyla, etrafımızda değiştirebileceğimiz risk faktörlerinden ne kadar uzak durulabilir ve kaçınılırsa AR prevalansının o kadar azaltılabileceği düşünülebilir.…”
Section: Alerjik Rinit Gelişimi Için Risk Faktörü Olan Bozukluklarunclassified
“…It is found that the asthma prevalence 6.6%. After that, Kurt [17] evaluated the prevalence of risk factors for asthma and allergic diseases in Turkey.…”
Section: Introductionmentioning
confidence: 99%